Evaluation of an occupational therapy led Paediatric Burns Telehealth Review Clinic: exploring the experience of family/carers and clinicians - Debra Phillips; Lauren Matheson; Tilley Pain; Gail Kingston (James Cook University, 2022)
Introduction: Children with deep-partial or full-thickness burns often require complicated post-surgical care and rehabilitation, including specialist occupational therapy (OT) intervention, to achieve optimal outcomes. Those from rural and remote areas rarely have access to these services and must travel to a tertiary referral hospital to access follow-up, placing them at higher risk of complications and poorer outcomes. The OT-Led Paediatric Burn Telehealth Review (OTPB) Clinic, based at Townsville University Hospital in northern Queensland, Australia, was set up to address this inequity. The aim of this study was to investigate the experience of both family members and clinicians in using the OTPB Clinic. Methods: A qualitative approach, guided by interpretive phenomenology, was used. Eight family members and six clinicians participated in semi-structured interviews conducted by phone or telehealth. Thematic analysis was used to identify key themes. Results: Four major themes were derived through thematic analysis: continuity of care, family-centred care, technology and building of rural capacity. Conclusion: Family and clinicians confirm benefits of a telehealth service for delivering care to rural and remote children after burn injury. The results show this expanded-scope, OT-led telehealth model provides quality patient-centred and expert clinical advice within local communities and builds the skill and capacity of local clinicians. Areas for service enhancement were uncovered. This telehealth model can be translated to other clinical subspecialties across Australia.